2 Corinthians - Guthrie, George H., 1959- (Grand Rapids, Michigan : Baker Academic a division of Baker Publishing Group, 2015)
In this addition to the award-winning BECNT series, a respected New Testament scholar offers a substantive evangelical commentary on 2 Corinthians. George Guthrie leads readers through the intricacies of literary structure, word meanings, cultural backdrop, and theological proclamation, offering insights applicable to modern ministry contexts. As with all BECNT volumes, this commentary features the author's detailed interaction with the Greek text; extensive research; thoughtful, chapter-by-chapter exegesis; and an acclaimed, user-friendly design. It admirably achieves the dual aims of the series -- academic sophistication with pastoral sensitivity and accessibility -- making it a useful tool for pastors, church leaders, students, and teachers. - Publisher.
The letter opening and prologue (1:1-11) -- Letter opening (1:1-2) -- Prologue (1:3-11) -- The integrity of Paul's ministry (1:12-7:16) -- Why Paul did not come directly to Corinth (1:12-2:13) -- Paul's reflections on authentic ministry (2:14-7:4) -- When Titus arrived in Macedonia : the happy result when the Corinthians respond well (7:5-16) -- The ministry of giving (8:1-9:15) -- Paul's exhortation to finish the collection (8:1-15) -- Titus's mission (8:16-9:5) -- Reflections on resources for giving and the results (9:6-15) -- Paul confronts the malignant ministry of his opponents (10:1-13:13) -- Present or absent, Paul's authority is the same (10:1-11) -- Proper and improper boasting (10:12-18) -- Paul boasts like a fool to stop the false apostles (11:1-12:13) -- Preparation for the third visit (12:14-13:10) -- Closing exhortations, greetings, and benediction (13:11-13).
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc